Disturbances of the cognitive functions of vehicle drivers in selected diseases - Łoś, Rafał; Latała-Łoś, Ewa (Medical Studies/Studia Medyczne, 2021)
Cognitive dysfunctions such as memory, attention, and orientation may occur in many disease entities, including those not included in the sphere of mental disorders. Their presence can significantly affect the ability to drive vehicles and road safety. The literature on the subject is dominated by studies assessing the functioning on the road of people driving vehicles with diagnosed cognitive disorders of various aetiologies. It is natural to divide them into disorders resulting from the pathology of the central nervous system and cognitive dysfunctions present in the course of typically somatic diseases. Assessment of identified abnormalities usually involves several stages, but the most documented method of evaluating disorders is neuropsychological examination.